THE EFFECTIVENESS OF CHITOSAN NATURAL SOURCES ON PULP TISSUE REGENERATION - Aisya Nadhifa Ahmad; Muhammad Yanuar Ichrom Nahzi; Juli Harnida Purwaningayu (FKG Unlam, 2023)
Background: Dental pulp plays a role in forming dentin, providing nutrition, and sensing harmful stimuli to the tooth. Pulp damage can occur due to physical, chemical, and biological factors. A regenerative therapy was developed so that the pulp can regenerate its tissue and the teeth can survive in the oral cavity with vital conditions. Tissue engineering is a principle developed in the treatment of pulp tissue regeneration. The main elements of tissue engineering are stem cells, scaffolds, and growth factors. Scaffolds are elements that support cell organization, migration, proliferation, differentiation, and vascularization. One example of a biomaterial that can be used as a scaffold is chitosan. Chitosan has been proved to be suitable as a biomedical material because it has several beneficial properties including increasing cell proliferation, attachment, and differentiation. Purpose: This study aims to determine the most effective natural ingredient chitosan for pulp tissue regeneration. Methods: This study used the literature review method with a narrative review procedure. The literature was searched using Google Scholar, Science Direct, ProQuest, and PubMed. Results: The results of the study from 6 articles showed that chitosan from shrimp, crab, and mushroom had the potential to increase pulp tissue regeneration in terms of 3 indicators (cell proliferation, attachment, and differentiation). Conclusion: The most effective chitosan from natural sources for pulp regeneration is shrimp chitosan and mushroom chitosan. Keywords: Chitosan, Natural Sources, Pulp Tissue Regeneration